All American boys - Reynolds, Jason (A Caitlyn Dlouhy Book / Atheneum, 2017)
"When sixteen-year-old Rashad is mistakenly accused of stealing, classmate Quinn witnesses his brutal beating at the hands of a police officer who happens to be the older brother of his best friend"--OCLC.